2006
DOI: 10.1177/0148607106030005433
|View full text |Cite
|
Sign up to set email alerts
|

Oral Rehydration for Viral Gastroenteritis in Adults: A Randomized, Controlled Trial of 3 Solutions

Abstract: Gatorade and N-ORS seem to be as effective as Pedialyte in correcting dehydration and in improving bowel symptoms. All 3 solutions were safe. Unlike other groups, hypokalemia persisted in the Gatorade group. Gatorade and N-ORS may be effective in the treatment of dehydration associated with mild viral gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Individuals suffering from diarrhea are typically defined as having a daily stool weight in excess of 216 200 g and a recent study reported mean stool weights of 750 g in persons with diarrhea (Rao, 2006); 217 a Uniform distribution was used to represent faecal weights for ill individuals, making the 218 assumption that all infected individuals have diarrhea (secondary attack rate counts only people who 219 are symptomatic). 220…”
Section: ) 215mentioning
confidence: 99%
“…Individuals suffering from diarrhea are typically defined as having a daily stool weight in excess of 216 200 g and a recent study reported mean stool weights of 750 g in persons with diarrhea (Rao, 2006); 217 a Uniform distribution was used to represent faecal weights for ill individuals, making the 218 assumption that all infected individuals have diarrhea (secondary attack rate counts only people who 219 are symptomatic). 220…”
Section: ) 215mentioning
confidence: 99%
“…During a diarrheal illness, a net secretion of fluids occurs because of a failure to absorb fluids normally or because of mucosal injury or toxin-induced excessive secretion. 9 When the colon cannot absorb this excessive fluid, it is excreted as diarrhea. Electrolyte imbalance can result with high-volume diarrhea.…”
Section: Complicationsmentioning
confidence: 99%
“…Without adequate glucose, the solution would not be absorbed and would only contribute to the volume of diarrhea. 9 Likewise, beverages with a higher glucose-to-sodium ratio, such as in fruit juices and soda, will increase diarrheal loss. Therefore, oral rehydration solutions must include glucose and sodium in the correct ratio and be palatable to encourage their consumption.…”
Section: Oral Rehydration Therapy For Mild To Moderate Viral Gastroenmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport and uptake of fluid restores plasma volume, promotes total body rehydration, and allows the individual to survive. Debate still exists as to the ideal ratio of sodium to glucose, 64 but it is generally believed that a 2:1 ratio of sodium to glucose is optimal to activate the transporter. 65 …”
Section: Acute Diarrheamentioning
confidence: 99%